Comparison of Clinical Outcomes of Orthogonal Versus Single Posterior Plating for Internal Fixation of Distal Humeral Extra-Articular Fractures - Qureshi, Bilal Ahmad; Amin, Muhammad Suhail; Khan, Ahmad Mushtaq; Rehman, Hafiz Faiz ur (Pakistan Armed Forces Medical Journal, 2025)
Objective: Complications are frequently linked to traditional treatment strategies for distal humeral fractures such as dual column plating. The study’s objective is to compare outcomes of osteosynthesis by a single dorsolateral plate in extra-articular distal humeral fractures with conventional bi-columnar fixation in terms of clinical results and radiological union. Study Design: Prospective Comparative Study. Place and Duration of Study: Department of Orthopedic Surgery, Combined Military Hospital, Rawalpindi Pakistan, from Oct 2022 to Sep 2023. Methodology: Forty skeletally matured patients, with closed distal humeral extra-articular fractures were sequentially enrolled into two groups. All patients underwent open reduction internal fixations of fractures using the same Alonso-Llames approach with single dorsolateral plating in group A and dual orthogonal plating in group B. Monthly follow-ups were ensured. Mayo Elbow Performance Score and Oxford Elbow Score were included to assess functional recovery, and a plain radiograph was used to evaluate union. Results: In group A, all fractures 20(100%) united successfully without any secondary displacement after a mean timeframe of 5.5 months. In group B, union rate of 19(95%) was observed (p=0.31). Postop pain was recorded to be significantly less in single plating.(VAS at 2 weeks p=0.006 and 4 weeks)(p=0.012). Higher elbow range of motion was restored with uni columnar fixation (124.90±3.64) than bicoulmnar construct (116.00±3.64)(p<0.001). Both functional scores were found to be considerably better in dorsolateral palting [MEPS=92.50 (100.00–85.00), OES=91.67 (95.83–85.93)] as compared to orthogonal plating (MEPS=85.00) (93.75–85.00), OES=80.20 (85.41–72.91)] (MEPS) p=0.021, OES (p<0.001). Conclusion: The current study suggests that single posterior ... ..